COMPETITION PREP STRUCTURE OF HIGHLY QUALIFIED PARAACADEMIC ROWERS - Mamajonova , Sevara; Mamajonov , Muminjon (Journal of Contemporary World Studies, 2024)
This study aims to analyze the relevance of the structure of pre-competition training of highly qualified para-academic rowers in Uzbekistan. The importance of this category of athletes in the development of rowing in our country, as well as the need to improve training methods and programs in order to achieve high results in international competitions, will be considered.